Genetic Diversity in Maize (Zea mays L.) Inbred Lines (The Agriculturists, 2012)
Thirty yellow inbred lines of normal maize were evaluated for thirteen parameters at the experimental field of Hajee Mohammad Danesh Science and Technology University during 2010-11 to study the genetic divergence using multivariate analysis. The thirty inbreds fell into six distinct clusters. The intra-cluster distances in all the six clusters were more or less low, indicating that the genotypes within the same cluster were closely related. The highest inter-cluster distance was observed between cluster I and cluster IV and the lowest between the cluster II and III. The cluster V and cluster IV contained the highest (9) and lowest (1) number of genotypes, respectively. Cluster VI showed the highest mean values for kernel yield and all the yield contributing traits except days to 50% tasseling and 50% silking. Cluster II had the lowest mean values for ear height and ear length. Days to maturity and ear diameter showed maximum contribution towards total divergence among different characters. Based on medium to high inter-cluster distances, six inbred lines viz. ML06, ML10, ML14, MK19, ML25 and ML26 were selected for hybrid program. Development of hybrids utilizing these genotypes has the chance to obtain higher heterosis with high performing crosses.DOI: http://dx.doi.org/10.3329/agric.v10i1.11066The Agriculturists 2012; 10(1): 64-70